Association of MTR and MTRR genes and oral health-related quality of life in children with dental caries - Lívia Azeredo Alves ANTUNES; Walter FIALHO; Thais de Oliveira FERNANDES; Camila DUARTE; Jhenyfer da Silva TAVARES; Erika Calvano KÜCHLER; Leonardo Santos ANTUNES (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aimed to assess whether genetic polymorphisms in MTR and MTRR are potential biomarkers of oral health-related quality of life (OHRQoL) in children with caries. A cross-sectional study was designed wherein pairs of parents/caregivers and children (aged two-five years) were selected. Clinical examination was used to detect dental caries, which were classified as low-severity and high-severity caries. The Early Childhood Oral Health Impact Scale (ECOHIS) questionnaire was used to assess OHRQoL. Genomic DNA extracted from the saliva was used to analyze two missense genetic polymorphisms: MTR (rs1805087) and MTRR (rs1801394). Mann-Whitney non-parametric test was used to analyze candidate genes with OHRQoL scale and domain, with a significance level of p≤0.05. MTR (rs1805087) was found associated (p = 0.05) with children's OHRQoL subscale scores in the dominant model (GG + AG). Genetic polymorphisms in MTR may increase the risk of poor OHRQoL in children with caries. Further studies are needed to investigate genetics, molecular factors, and OHRQoL.